Enterprise Digital Transformation: Leveraging AI/ML and Automation for Operational Excellence - Varun Narayan Bhat, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the transformative impact of Artificial Intelligence (AI), Machine Learning (ML), and automation technologies on enterprise digital transformation within the technology sector. It explores how leading organizations leverage predictive analytics, intelligent automation, and real-time decision-making capabilities to optimize their operations and enhance customer experiences. Through detailed case studies and industry analysis, it demonstrates the significant benefits of AI/ML integration across software development, IT service management, and cloud operations. While addressing critical challenges such as ethical AI deployment, data complexity management, and workforce adaptation, this article provides strategic insights into emerging trends like explainable AI and edge computing. This article underscores the strategic imperative for technology enterprises to align their AI/ML investments with long-term business objectives, highlighting the role of hyper automation in creating resilient and intelligent digital ecosystems that drive sustainable competitive advantage in the rapidly evolving technology landscape.
Keywords: Enterprise Digital Transformation; Artificial Intelligence and Machine Learning; Operational Automation; Technology Innovation; Predictive Analytics